Effect of the numerical viscosity on reproduction of mean and turbulent flow fields in the case of a 1:1:2 single block model. Issue 191 (August 2019) - Ikegaya, N.; Okaze, T.; Kikumoto, H.; Imano, M.; Ono, H.; Tominaga, Y.
Abstract: Large-eddy simulations were performed for the velocity fields around a 1:1:2 single block model to clarify the effect of the numerical viscosity in different advection schemes. Six types of advection schemes with different numerical viscosities were employed: second-order central, first-order upwind, and blending schemes with ratios of 95:5, 90:10, 80:20, and 60:40. The central scheme alone or the blending schemes predicted values of the mean and turbulent kinetic energy that were comparable with those of the experiments, whereas the upwind scheme significantly underestimated the experimental values. In addition to the comparison with the experimental data, the turbulent flow fields among the schemes were compared by deriving the probability and power spectral densities. Blending of the upwind scheme indeed reduced the turbulence energy contribution at high frequency. However, such a reduction in energy became influential to the reproduction of the turbulent flows only when damping of the peak spectral energy occurred. The reduction of the statistical values became ∼10% when blending the upwind scheme by 20%. In contrast, a strong or weak velocity, evaluated by the percentile velocities, was more sensitive to the selection of the advection scheme than the mean velocities. Highlights: Central and blending schemes predict turbulence statistics comparable with experiment. Blending of upwind scheme reduces turbulence energy contribution at high frequency. Reduction in TKE influences turbulent flow fields only when peak energy damped. Percentile velocities are more sensitive to selection of advection scheme.